2021
DOI: 10.1002/aic.17301
|View full text |Cite
|
Sign up to set email alerts
|

Application of offset‐free Koopman‐based model predictive control to a batch pulp digester

Abstract: This work presents the application of a Koopman operator approach to a batch pulp digester. To manufacture paper products with desired properties, it is essential to consider both macroscopic and microscopic attributes of pulp. However, the complexity of multiscale dynamics of pulping processes hinders proper control system design. Therefore, we utilize extended dynamic mode decomposition (EDMD), which is based on Koopman operator theory, to derive a global linear representation of a pulp digester. Then, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The overall performance of the NN model is better than models with three linearization points but worse than models with five linearization points and the subspace LTI model.Remark Comparing Figures 6 and 8, it is observed that for EMPC, multiple approximation models have responses with significant offsets compared to the original model. With various works done on offset‐free MPC, [ 46–48 ] it is natural to consider if the same approaches can be adopted for EMPC applications. The answer is no, in general.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall performance of the NN model is better than models with three linearization points but worse than models with five linearization points and the subspace LTI model.Remark Comparing Figures 6 and 8, it is observed that for EMPC, multiple approximation models have responses with significant offsets compared to the original model. With various works done on offset‐free MPC, [ 46–48 ] it is natural to consider if the same approaches can be adopted for EMPC applications. The answer is no, in general.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing Figures 6 and 8, it is observed that for EMPC, multiple approximation models have responses with significant offsets compared to the original model. With various works done on offset-free MPC, [46][47][48] it is natural to consider if the same approaches can be adopted for EMPC applications. The answer is no, in general.…”
Section: Economic Model Predictive Controlmentioning
confidence: 99%
“…( 15). Several works employed a linear Koopman approach in identification and control studies and observed a higher performance over conventional linear identification methods [27][28][29][30][31][32][33][34]. However, when significant nonlinearity is present, Eq.…”
Section: Koopman Theory For Controlled Systemsmentioning
confidence: 99%
“…Specifically, we employ Koopman theory to identify low-order latent dynamics describing the nonlinear system evolution. While the existing literature on Koopman modeling for control has focused on linear [27][28][29][30][31][32][33][34] and bilinear [35][36][37][38] forms, we consider a MIMO Wiener structure. As we show, when combined with Koopman theory, the Wiener structure provides strong model reduction capabilities beyond those of linear and bilinear models.…”
Section: Introductionmentioning
confidence: 99%
“…An ILC controller distills information from the tracking error in the past to better tune the control input of the present trial (termed “batch” thereafter), etc., until achieving the perfect tracking of the given set-point profile. Notably, over the past decades, a multitude of achievements for better ILC have been witnessed both theoretically and practically. Encouraging endeavors of applying ILC in practice include injection molding, bioreactors, and batch chemical reactors, whereas considerable theoretical efforts are devoted to answering the longstanding questionhow to synthesize an ILC controller against various uncertainties. Such efforts include the introduction of feedback, multipoint compensation, adaptive tuning, , and optimal design for linear systems and nonlinear systems.…”
Section: Introductionmentioning
confidence: 99%